The consequences of the economic crisis in radiology (Insights Imaging, 2015)
ABSTRACT: The effects of the economic crisis have led to complex problems in radiology. The crisis has led to a reduction in the turnover of imaging equipment. This reflects on the quantity and quality of output, an aspect which is worsened by the contraction of the radiology market, late payments on supplies, and competitive procurement of medical goods centralized on a regional or national level. Many local and national institutions have operated with significant reductions of reimbursement for procedures, forcing a reorganization of facilities, manpower, and equipment. The reduction in operating margins of the industry has resulted in a reduction of invested capital for projects of industrial R&D and direct or indirect sponsorship. The quality of care will be affected with less comfortable conditions, reduction of local availability of radiologists, and failure to invest in lower dose equipment to control population medical radiation exposure. The crisis resulted in a reduction in the number of graduates in medicine and scholarships for specialization induced by linear cuts will result in a drastic reduction of radiological specialists. This will favour the development of teleradiology services, with the risk of accelerating the demedicalisation of radiology departments, and isolation of the professionals. MAIN MESSAGES: • The economic crisis has led to reduction in the turnover of imaging equipment. • The economic crisis has led to reductions of reimbursement for procedures. • The economic crisis has led to reductions in operating margins of the industry. • The economic crisis has led to contraction of quantity and quality of output. • The economic crisis resulted in demedicalisation of radiology departments and isolation of professionals.